Recovering Greater Fungal Diversity from Pristine and Diesel Fuel Contaminated Sub-Antarctic Soil Through Cultivation Using Both a High and a Low Nutrient Media Approach - Ferrari, Belinda C.; Zhang, Chengdong; Van Dorst, Josie (Frontiers in Microbiology, 2011)
Novel cultivation strategies for bacteria are widespread and well described for recovering greater diversity from the “hitherto” unculturable majority. While similar approaches have not yet been demonstrated for fungi it has been suggested that of the 1.5 million estimated species less than 5% have been recovered into pure culture. Fungi are known to be involved in many degradative processes, including the breakdown of petroleum hydrocarbons, and it has been speculated that in Polar Regions they contribute significantly to bioremediation of contaminated soils. Given the biotechnological potential of fungi there is a need to increase efforts for greater species recovery, particularly from extreme environments such as sub-Antarctic Macquarie Island. In this study, like the yet-to-be cultured bacteria, high concentrations of nutrients selected for predominantly different fungal species to that recovered using a low nutrient media. By combining both media approaches to the cultivation of fungi from contaminated and non-contaminated soils, 91 fungal species were recovered, including 63 unidentified species. A preliminary biodegradation activity assay on a selection of isolates found that a high proportion of novel and described fungal species from a range of soil samples were capable of hydrocarbon degradation and should be characterized further.